Analisis Pengaruh Promosi Penjualan, Persepsi Manfaat dan Persepsi kemudahan Penggunaan terhadap Keputusan Penggunaan Gopay pada Mahasiswa UPN “Veteran” Jawa Timur - Lucyana Mirah Dyas; Sugeng Purwanto (IPM2KPE, 2024)
This research aims to analyze the influence of sales promotions, perceived benefits, and perceived ease of use on the decision to use GoPay. The research method used in this research is a quantitative method. Sampling used a non-probability sampling method with convenience sampling technique. Data analysis was carried out using the SEM method which is based on components, with PLS as an analysis tool. The results of this research are that the sales promotion variables (X1), perceived benefits (X2), and perceived ease of use (X3) have a positive and significant effect on the decision to use Gopay among UPN